Metaphor as an object of the synergy paradigm study - Guliyev, Fakhraddin Abdulkerim Oglu (Linguistics and Culture Review, 2021)
The article investigates the ontognoseological properties of metaphor from the point of view of the synergetic paradigm. By the principles of synergetic science, metaphor is considered as a nonlinear system category that performs a system-forming, heuristic, generalizing function. With the help of the principle of subordination, complex systems are described through a limited number of order parameters, as a result of which information is compressed without loss. The metaphor has its origins in the economy: as a method of abstraction, the transition from the infinite to the finite, and the reduction of lexical means. Metaphor is a way of transmitting an idea that has a methodological significance, i.e. one theoretical system is translated into another and one system is investigated through another, simpler system. Metaphor as a dynamic formation establishes connections between objects of different orders and processes in their development in space and time, which allows you to explore metaphors using the principles of synergetics.